ANXIETY LEVELS DURING MENARCHE AMONG FEMALE STUDENTS AT STATE JUNIOR HIGH SCHOOL 1 OF AYAH - Sumarsih, Tri; Nurfadillah, Marina; Asti, Arnika Dwi (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
Menarche is the early menstruation that usually occurs at the age of 10-14 years. It is the culmination of a series of changes in adolescents who are stepping on adulthood. These changes bring about various questions, feelings of confusion, fear and anxiety. This reaserah to know the anxiety during menarche (first menstruation) of female students of State Junior High School 1 of Ayah. This study uses descriptive method with cross sectional approach. The populations are all female students of State Junior High School 1 of Ayah who have experienced menarche. Samples were taken by using simple random sampling technique on 170 respondents. Instrument used in this study was DASS (Depression Anxiety Stress Scale). Data was analyzed by using univariate analysis. Based on the research conducted, there were 67 respondents (39.4%) experienced light anxiety during menarche. It is advisable for adolescents who are going into adulthood to get lot of knowledge about menarche.